Workshop dan Pameran Pembuatan Produk Ecoprint Mengunakan Teknik Pounding dengan Bahan Daun Eksotik di Sekitar Tempat Tinggal: Pengabdian - Yohanes Jhony Kurniawan; Heppy Julianto; Mirnawati (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This Community Service (PKM) activity; To improve understanding of advanced training in Ecoprint Product Making Entrepreneurship Using Pounding Techniques with Exotic Leaf Materials from Around the Residence. To increase promotion of Ecoprint Product Making Entrepreneurship Using Pounding Techniques with Exotic Leaf Materials from Around the Residence. With the Advanced Training method and Ecoprint Product Exhibition. Participants who attended this PKM were 17 people. The results of this PKM are 3 ecoprint products Using Pounding Techniques with Exotic Leaf Materials from Around the Residence, and have been exhibited through Instagram social media, and other conventional media.